From Victim to Minister's Advisor: A Personnal View of Child Protection in France - Greco, Céline (Frontiers in Pediatrics, 2021)
In France, maltreatment of children, that mean “physical, sexual or emotional maltreatment or neglect of a child” is a very underestimated phenomenon, yet it is running rampant. The various causes of child abuse are subject to denial, and the ensuing delay of identification of victims is profoundly damaging. As a medical doctor and survivor of child abuse, I have a clear vision of the shortcomings of our child protection system. Non-recognition or late recognition of cases of child abuse is directly related to a lack of knowledge and training on this subject, which leads to weaknesses both in terms of detection and reporting of potential cases. Once the children are identified, they need to receive proper care that should not be limited to the social aspects. Indeed, the victims of abuse suffer from important repercussions on their physical and mental health. Without proper care, their health as adults will be severely impacted. These children require specific care and an adapted health care pack, as well as inclusion in the child protection framework. The task force “Child health in child protection “ that I manage has suggested the creation of a standardized healthcare protocol for child victims of abuse, with psychological and medical costs fully covered by the Government, especially regarding clinical psychologists and psycho-motor therapists.